2003
DOI: 10.1128/jvi.77.5.3247-3256.2003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Point Mutations in the Major Capsid Protein of Beet Western Yellows Virus on Capsid Formation, Virus Accumulation, and Aphid Transmission

Abstract: Point mutations were introduced into the major capsid protein (P3) of cloned infectious cDNA of the polerovirus beet western yellows virus (BWYV) by manipulation of cloned infectious cDNA. Seven mutations targeted sites on the S domain predicted to lie on the capsid surface. An eighth mutation eliminated two arginine residues in the R domain, which is thought to extend into the capsid interior. The effects of the mutations on virus capsid formation, virus accumulation in protoplasts and plants, and aphid trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
76
3
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(82 citation statements)
references
References 22 publications
2
76
3
1
Order By: Relevance
“…Based on sequence alignments with other icoahedral viruses whose structures were known, two of the surface domains were located on loops known to be important antigenic sites on structurally related viruses. More recently, independent structure models were developed for the CP of two members of the genus Polerovirus in the Luteoviridae, PLRV and Beet western yellows virus (BWYV) (2,31). The models support the data from the epitope-mapping studies and locate the surface epitopes on the loops between ␤-strands G and H and between ␤-strands B and C. Although the best-fit structure models for PLRV and BWYV both locate epitope 10 (32) on the G-H loop, the structural features of the loop differed between these closely related viruses (2).…”
mentioning
confidence: 99%
“…Based on sequence alignments with other icoahedral viruses whose structures were known, two of the surface domains were located on loops known to be important antigenic sites on structurally related viruses. More recently, independent structure models were developed for the CP of two members of the genus Polerovirus in the Luteoviridae, PLRV and Beet western yellows virus (BWYV) (2,31). The models support the data from the epitope-mapping studies and locate the surface epitopes on the loops between ␤-strands G and H and between ␤-strands B and C. Although the best-fit structure models for PLRV and BWYV both locate epitope 10 (32) on the G-H loop, the structural features of the loop differed between these closely related viruses (2).…”
mentioning
confidence: 99%
“…Negative controls (sample buffer) showed absorbance values of less than 0.015. Brault et al, 1995;Brault et al, 2000). However, the molecular aspects of luteovirids-vector interactions and the involvement of RTD in the transmission process are essentially based on work with BYDV and BWYV.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on the role of the viral capsid-associated proteins of luteoviruses have shown that the BWYV RTD protein is indispensable for transmission by Myzus persicae (Sulz. ), and harbour determinants which mediate circulation of the virus in the aphid (Brault et al, 1995). The recognition and movement of BWYV into the aphid vector hemocoel is greatly reduced in RTD deficient mutants, suggesting an important role for this protein in virus recognition and the trans-cellular transport process (Reinbold et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations